2013
DOI: 10.1063/1.4811408
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of concurrent energy harvesting from ambient vibrations and wind using a single piezoelectric generator

Abstract: First and foremost, I thank God for all the blessings he bestowed on me during my life, and for giving me such a great opportunity, along with the patience and enthusiasm necessary to complete this Ph.D dissertation. Secondly, I especially thank my Thesis advisor, Dr. Mohammed F. Daqaq, for his invaluable support and advice throughout my time in Clemson. I am very blessed to have him as a friend and a mentor. I thank him for patiently teaching me innumerable lessons pertinent to research and also for motivatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
49
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(54 citation statements)
references
References 71 publications
0
49
0
Order By: Relevance
“…Complex motions were predicted under the combined excitations by analytical solutions based on the normal form method, which were validated by numerical integrations. In a subsequent study, Bibo and Daqaq [68] performed experiment to demonstrate these complex motions by attaching the harvester prototype to a seismic shaker which provided the harmonic base excitation and putting the whole system in a wind tunnel which provided the aerodynamic loads. Below the flutter speed, it was found that the flow serves to amplify the output power from base excitations.…”
Section: Energy Harvesters Based On Modal Convergence Fluttermentioning
confidence: 99%
See 1 more Smart Citation
“…Complex motions were predicted under the combined excitations by analytical solutions based on the normal form method, which were validated by numerical integrations. In a subsequent study, Bibo and Daqaq [68] performed experiment to demonstrate these complex motions by attaching the harvester prototype to a seismic shaker which provided the harmonic base excitation and putting the whole system in a wind tunnel which provided the aerodynamic loads. Below the flutter speed, it was found that the flow serves to amplify the output power from base excitations.…”
Section: Energy Harvesters Based On Modal Convergence Fluttermentioning
confidence: 99%
“…Recently, the field of small-scale wind energy harvesting has experienced dramatic growth [14][15][16][17][18][19][20][21]. Researchers have reported studies on harnessing wind power using miniaturized windmills (e.g., [22]) or making use of aeroelastic instabilities such as vortex-induced vibration (VIV) (e.g., [23]), galloping (e.g., [24,25]), aeroelastic flutter (e.g., [26]), and wake galloping (e.g., [27]).…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the operating wind speed, piezoaeroelastic energy harvesters can be designed and deployed in different locations, such as structure's surface, ventilation outlets, rivers, etc., to power sensors or actuators. Several investigations have focused on harvesting energy from flow-induced vibrations, such as vortex-induced vibrations of circular cylinders, 1-4 flutter of airfoil sections, [5][6][7][8][9][10][11][12][13] wake galloping, 14,15 and galloping of prismatic structures. [15][16][17][18][19][20][21][22] The transverse galloping phenomenon has shown a promise for effective energy harvesting.…”
mentioning
confidence: 99%
“…[1][2][3][4][5]. There are many energy sources for power generation [6][7][8], and the mechanisms harvesting two or more energy can attain a higher energy conversion efficiency [9,10].…”
Section: Introductionmentioning
confidence: 99%